2022
DOI: 10.1080/21655979.2022.2047404
|View full text |Cite
|
Sign up to set email alerts
|

LEM domain containing 1 promotes pancreatic cancer growth and metastasis by p53 and mTORC1 signaling pathway

Abstract: Pancreatic cancer (PC) is a common type of malignancy originating from the epithelium of the pancreatic duct, with the most lethal feature and worst prognosis. LEM domain containing 1 (LEMD1) is overexpressed in multiple tumor tissues and plays a key role in cancer carcinogenesis and progression. However, little is known about the potential of LEMD1 in PC. In this study, we explored the clinical values, as well as the potential roles and mechanisms of LEMD1 in PC. We, for the first time, showed that LEMD1 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…In human cytomegalovirus infection, there is association of CCR5Δ32 deletion and human cytomegalovirus infection with colorectal cancer in Tunisia [61]. Kaposi sarcoma-associated herpesvirus infection regulates proliferation of glioma stem-like cells [62], relieves the Warburg effect through p53 activation, thereby inhibiting breast cancer cell growth [63], inhibits renal cancer cell growth by regulating the p53 signaling pathway [48], suppresses lung cancer growth by activating the p53 signaling pathway [64], promotes cholangiocarcinoma cell proliferation, migration, and invasion by decreasing p53 expression [65], and promotes pancreatic cancer growth and metastasis through the p53 transcriptional pathway [66]. In addition, th17 cells play a key role in autoimmunity and their cell differentiation contributes greatly to the treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In human cytomegalovirus infection, there is association of CCR5Δ32 deletion and human cytomegalovirus infection with colorectal cancer in Tunisia [61]. Kaposi sarcoma-associated herpesvirus infection regulates proliferation of glioma stem-like cells [62], relieves the Warburg effect through p53 activation, thereby inhibiting breast cancer cell growth [63], inhibits renal cancer cell growth by regulating the p53 signaling pathway [48], suppresses lung cancer growth by activating the p53 signaling pathway [64], promotes cholangiocarcinoma cell proliferation, migration, and invasion by decreasing p53 expression [65], and promotes pancreatic cancer growth and metastasis through the p53 transcriptional pathway [66]. In addition, th17 cells play a key role in autoimmunity and their cell differentiation contributes greatly to the treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Hamada et al mentioned in their research that mitotic spindle assembly might be a common feature of lung cancer and PAAD [31]. Cao et al found that the gene could affect the cell growth process of PAAD by inhibiting p53 and activating the mTORC1 signaling pathway when exploring the mechanism of LEMD1 in PAAD [32]. Zhang et al observed that loss of IL17/IL17R signaling led to growth inhibition of PAAD [33].…”
Section: Discussionmentioning
confidence: 99%
“…Normal human thyroid (Nthy-ori 3–1) and PTC (TPC-1 and B-CPAP) cell lines were purchased from Procell (Wuhan, China). The cells were cultured in a standard incubator at 37°C with 5% CO 2 in RPMI-1640 (Gibco; Thermo Fisher Scientific, Waltham, MA, USA) with 10% fetal bovine serum (Gibco) and 1% penicillin/streptomycin [ 20 ]. The cells were treated with actinomycin D (2 μg/mL; Sigma-Aldrich, St. Louis, MO, USA) to analyze the mRNA stability.…”
Section: Methodsmentioning
confidence: 99%